PENGALAMAN MAHASISWA PGSD PAPUA MENGGUNAKAN QUIZIZZ DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN - Rusli, Tiffany Shahnaz (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The use technology-based learning media has become a crucial innovation in improving the quality of education, including in Papua. This study aims to analyze the experiences of PGSD students at Universitas Cenderawasih in using Quizizz as a learning medium in the Civic Education course. A qualitative approach with a descriptive method was employed, utilizing interviews, obsevations, and an analysis of learning evaluation results as data collection techniques. The findings reveal that most students perceive Quizizz as providing a more engaging and interactive learning experience through gamification features such as leaderboards and instant feedback. This positively impacted students learning motivation, with a 15% increase in average evaluation scores compared to conventional methods. However, the study also identified significant challenges, particularly limited internet access, especially for students residing in remote areas of Papua. The study concludes that Quizizz is an effective learning medium in supporting students competency achievement, although infrastructure challenges remain a major obstacle. Developing offline features and improving infrastructure support are essential to ensure the sustainability of this media’s implementation. Future research is recommended to explore Quizizz’s application in other courses and its integration with project-or problem-based learning methods.